Conserved Amino Acids Residing Outside the Voltage Field Can Shift the Voltage Sensitivity and Increase the Signal Speed and Size of Ciona Based GEVIs - Sepehri Rad, Masoud; Cohen, Lawrence B.; Baker, Bradley J. (Frontiers in Cell and Developmental Biology, 2022)
To identify potential regions of the voltage-sensing domain that could shift the voltage sensitivity of Ciona intestinalis based Genetically Encoded Voltage Indicators (GEVIs), we aligned the amino acids sequences of voltage-gated sodium channels from different organisms. Conserved polar residues were identified at multiple transmembrane/loop junctions in the voltage sensing domain. Similar conservation of polar amino acids was found in the voltage-sensing domain of the voltage-sensing phosphatase gene family. These conserved residues were mutated to nonpolar or oppositely charged amino acids in a GEVI that utilizes the voltage sensing domain of the voltage sensing phosphatase from Ciona fused to the fluorescent protein, super ecliptic pHluorin (A227D). Different mutations shifted the voltage sensitivity to more positive or more negative membrane potentials. Double mutants were then created by selecting constructs that shifted the optical signal to a more physiologically relevant voltage range. Introduction of these mutations into previously developed GEVIs resulted in Plos6-v2 which improved the dynamic range to 40% F/F/100 mV, a 25% increase over the parent, ArcLight. The onset time constant of Plos6-v2 is also 50% faster than ArcLight. Thus, Plos6-v2 appears to be the GEVI of choice.